Modelling unsaturated soil-structure interfacial behavior by using DEM. (September 2021) - Liu, Xin; Zhou, Annan; Shen, Shui-Long; Li, Jie; Arulrajah, Arul
Abstract: The interface between unsaturated soil and structure plays an important role in various geotechnical structures in natural environment. In this study, a series of three-dimensional numerical direct shear tests are conducted on a soil-structure interface under various suctions and normal stresses by using the discrete element method (DEM). The simulated macro-mechanical results match reasonably well with experimental data reported in the literature. During the shearing process, the micro-mechanical shearing properties between unsaturated soil and structure are investigated, including particle displacement, the magnitude and orientation of the contact force, and the magnitude and orientation of the capillary force. The influence of capillary cohesion on the macro- and micro-mechanical behavior of the interface changes non-monotonically with the suction increase. Samples with the suction (or degree of saturation) in the funicular regime usually show more distinct capillary cohesion effect compared with that in either capillary or pendular regimes. The capillary cohesion effect on unsaturated soil-structure interfacial behavior is weakened with increasing normal stress.